Research of infiltrates content of landfills of hard domestic wastes (HDW) (on the example of Lviv landfill) - Sereda, Andriy; Sliusar, Vira; Vronska, Nataliya; Malovanyy, Myroslav (Видавництво Львівської політехніки, 2017)
Work investigated composition of infiltrates of Lviv landfill HDW. An estimate is given of his influence on an environment and a microbiological analysis was conducted of the formed culture in infiltratу after pre-clean it by aeration.
Keywords: infiltrate; landfill of hard domestic wastes; maximum permissible concentration; microbiological culture